2015
DOI: 10.1007/978-3-319-22701-6_29
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Under the Desk: A Characterisation of Foot Movements for Input in a Seated Position

Abstract: Abstract. We characterise foot movements as input for seated users. First, we built unconstrained foot pointing performance models in a seated desktop setting using ISO 9241-9-compliant Fitts's Law tasks. Second, we evaluated the effect of the foot and direction in one-dimensional tasks, finding no effect of the foot used, but a significant effect of the direction in which targets are distributed. Third, we compared one foot against two feet to control two variables, finding that while one foot is better suite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The previous projects demonstrated how the same principle of motion correlation can be used with two different modalities, namely gaze and mid-air hand gestures. However, it is easy to imagine how the technique could work with other human movement modalities, such as head [35] or feet movements [58]. With this in mind, we developed TraceMatch, a computer vision technique that searches for matching movements in a video feed, effectively enabling interaction based on motion correlation regardless of the modality being used.…”
Section: Tracematchmentioning
confidence: 99%
“…The previous projects demonstrated how the same principle of motion correlation can be used with two different modalities, namely gaze and mid-air hand gestures. However, it is easy to imagine how the technique could work with other human movement modalities, such as head [35] or feet movements [58]. With this in mind, we developed TraceMatch, a computer vision technique that searches for matching movements in a video feed, effectively enabling interaction based on motion correlation regardless of the modality being used.…”
Section: Tracematchmentioning
confidence: 99%
“…Previous studies which have evaluated the ability for a single human subject to coordinate three hands together (trimanual activities) include 12 , who studied re-sizing, 13,14 who demonstrated the ability to control three hands with the natural limb and 15 who investigated the impact of adding a third hand to different bi-manual tasks of varying coupling level. From these studies it has been observed that human subjects can control three hands simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Related work generally assumes use of the hands for pointing (e.g., [61,52,5,34,13]) but work in other areas has shown that humans are equally natural at pointing with other parts of their body (literally, from head [45,38] to toe [58]). We reflect this in an approach that is input-agnostic and supports any body movement to be adopted for pointing, contrasting existing systems that are optimised for specific modalities such as tracking of hand gestures [48], head pose [54], or feet [56].…”
Section: Background and Related Workmentioning
confidence: 99%